Clinical Leadership Perspectives: Advancements in Manual Physical Therapy Practice with the Pakistani Context - Sarfraz, Maheen; Shakil ur Rehman, Syed; Ikram, Mehwish; Ikram, Maryam (International Health Review, 2023)
Physical therapy is a healthcare discipline that is dedicated to help individuals and patients in maintaining their health while optimizing their strength, function, and movements. Pakistan being a developing country, experiences a slower pace in the establishment of advancements in the medical professions. Whereas physical therapy is significantly improving day by day in Pakistan; additionally, this study aims to discuss the advances, in manual therapy concerning the physical therapy profession in Pakistan. This study aimed to evaluate the perception of clinical leadership and its recent advancements concerning the manual physical therapy practice in Pakistan for the preceding year. For this purpose, semi-structured interviews were conducted with 10 physical therapists from 5 different cities in Pakistan. Physical therapists with at least 10 years of clinical practice were included in the data collection. The interviews were audio/video recorded, data verbatim transcribed, and analyzed manually by open coding and in-vivo coding. Furthermore, thematic analysis was done to identify different elements of recent advancements concerning manual physical therapy by finding the appropriate patterns in the gathered data. The results showed that advancements occurred in the last decade, such as international certifications, workshops, hands-on practice and master programs. There is lack of awareness, gender barriers, and financial constraints in adopting new advancements. The focus was shifted more toward muscle energy technique and myofascial release. Modalities were preferred in the past for pain relief; however, in the recent decade, they have been replaced by manual therapy techniques. Pain management and prognosis are better with manual therapy. These advancements will be cost-effective for the patient. This study concluded that manual therapy in Pakistan has undergone a significant transformation during the last preceding years. There is still great potential for more advancement in manual therapy techniques in Pakistan.